Cystatin C and interleukin‐6 for prognosticating patients with acute decompensation of cirrhosis. Issue 4 (9th March 2021) - Padia, Gaurav; Mahajan, Bhawana; Kumar, Ajay; Sonika, Ujjwal; Dahale, Amol S; Sachdeva, Sanjeev; Dalal, Ashok; George, Roshan
Abstract: Background and Aim: Systemic inflammation and organ dysfunction/failure can complicate acute decompensation (AD) of cirrhosis with progression to acute‐on‐chronic liver failure (ACLF), leading to increased mortality. There are few studies on serum biomarkers predicting renal dysfunction (RD) or ACLF in AD. Serum cystatin C (CysC) and interleukin‐6 (IL‐6) were evaluated for predicting RD, ACLF, and mortality in AD patients. Methods: Consecutive AD patients seen from January 2018 to June 2019 were included. IL‐6 and CysC were measured in serum at the time of index presentation. Patients were followed for 90 days or until primary (development of RD) or secondary outcomes (development of ACLF or mortality). Multivariate analysis was performed to find whether CysC and IL‐6 can independently predict primary and secondary outcomes. Results: A total of 124 patients were screened; 88 patients were included. On follow up, 22 (27.3%) developed RD, 11 (11/57, 19.3%) developed ACLF, and 21 (24%) died. The CysC predicted RD (odds ratio [OR] 7.97, 95% confidence interval [CI] 2.70–23.53, P = 0.001) and ACLF (OR 5.486, 95% CI 1.456–20.6, P = 0.012) development. IL‐6 was not an independent predictor of RD ( P = 0.315), ACLF ( P = 0.168), and mortality ( P = 0.225). Conclusion: Serum CysC can predict the development of RD and ACLF in patients of cirrhosis with AD. Abstract : Our study evaluates prognostic efficacy of biomarkers like cystatin C and Interlekin 6 in patients with acute decompensation of cirrhosis. We found cystatin C predicted renal dysfunction and Acute on chronic liver failure but mortality in cirrhotic patients presenting with new onset decompensation while Interlekin 6 did not predicte these events.